1968
DOI: 10.1042/bj1080755
|View full text |Cite
|
Sign up to set email alerts
|

The osmotic behaviour of Sephadex and its effects on chromatography

Abstract: 1. Sephadex in bead form shows reversible changes of inner volume when immersed in solutions of a non-penetrating solute. These changes are in accordance with the theory of Flory (1953) for the swelling of gels. This makes possible the use of single beads for measuring the osmotic pressures of polymer solutions, up to or beyond 1kg./cm.(2). 2. Measurements of the inner volume of Sephadex G-200 by equilibrium dilution, at various concentrations of dextran 500, gave values in agreement with those obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 8 publications
2
37
0
Order By: Relevance
“…Although positive concentration dependence of elution volume for nonassociating proteins was observed in the early days of frontal gel chromatography on Sephadex [57], that effect has been traced to osmotic shrinkage of the gel beads in response to the difference between protein concentrations (and therefore pressures) in the mobile and gel phases [58]. However, the advent of high-performance…”
Section: Size-exclusion Chromatographymentioning
confidence: 99%
“…Although positive concentration dependence of elution volume for nonassociating proteins was observed in the early days of frontal gel chromatography on Sephadex [57], that effect has been traced to osmotic shrinkage of the gel beads in response to the difference between protein concentrations (and therefore pressures) in the mobile and gel phases [58]. However, the advent of high-performance…”
Section: Size-exclusion Chromatographymentioning
confidence: 99%
“…The results on the macroscopic shrinkage of Sephadex to be used in the present comparative study are those reported by Edmond et al (1968) and are given in Table 2. The shrinkage behaviours of Sephadex grades G-75, G-100 and G-200 are reported (columns 3, 5 and 7 of Table 2).…”
Section: Methodsmentioning
confidence: 81%
“…The shrinkage behaviours of Sephadex grades G-75, G-100 and G-200 are reported (columns 3, 5 and 7 of Table 2). The corresponding osmotic pressure of the solutions of this dextran can be calculated from xr/RT= c/1.53 x 10'+ 3.41 x 10-40+3.35 x 10-3c3 (Edmond et al, 1968) and are given in column 2 of Table 2. It is necessary, in turn, to find the concentrations of 'matched' dextrans that correspond to these osmotic pressures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations